Sistem Pendukung Keputusan Pemilihan Kain Terbaik Di Toko Crown Textile & Tailor Dengan Metode Simple Additive Weighting (SAW) - Sungguh Zebua; R. Mahdalena Simanjorang (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2021)
The retail business continues to grow rapidly along with the development of science and technology in the era of globalization, but the purchase of fabric is still done manually and not computerized, such as in choosing fabrics, only looking at the shape of the color and the price tag, if it is suitable and likes it is taken immediately without thinking what type of fabric to use. used for these clothes, when they have been made into clothes or clothes, do not match the criteria desired by consumers and many ready-made clothes are returned because the color becomes dull or faded, and does not match the desired motif. The problem in this study is to determine the selection of the best fabric using SPK with the Simple Additive Weighting (SAW) method in selecting the best fabric at Crown Textile Tailor built using PHP MyAdamin programming. The decision support system method used is Simple Additive Weighting (SAW), because it can determine the weight value for each attribute, through a ranking process selecting the best alternative from a number of alternative data, the results obtained are Viscose Rayon Fabrics worth 0.933, (Rank 1), Brukat Lace Fabrics are worth 0 .9 (Rank 2), Toyobo Cotton Fabric is worth 0.716 (Rank 3), Japanese Cotton Fabric is worth 0.700 (Rank 4).